Staffing of the Ukrainian SSR militia in 1945 - V. A. Grechenko (Bulletin of Kharkiv National University of Internal Affairs)
The main aspects of the USSR militia staffing in 1945 are revealed. The main directions of personnel work were as follows: 1) completion of staffing of militia bodies; 2) consolidation of personnel, primarily management; 3) creation of an effective reserve of nomination; 4) organization of training, improving the quality of preventive and educational work among personnel; 5) completion of the collection and search of personal files and bringing them into order, completion of a special inspection of those who joined the militia. During 1945, the PCIA (people's commissariat of internal affairs) of the Ukrainian SSR provided instructions on all these issues in the form of directives, reviews, written comments on the work and provided practical assistance on field trips. Specialists were trained in special courses in militia schools, whose activities were resumed in several cities of the republic. In 1945, 12,153 people came to recruit militia, and 5,906 people left and were released. A significant shortcoming in recruitment was staff turnover. The main reasons for the turnover in the police in 1945 were as follows: a) reduced admission requirements to the militia (recruited people without inspection by the medical commission, sometimes clearly disabled); b) insufficient verification of new recruits; c) weak educational work among the staff. Of the total number of those released in 1945: a) for illness, age and inadequacy – 4652 people; b) according to the materials of the special inspection – 1526 people; c) for moral and domestic decomposition, violation of labor discipline, personal desires and family circumstances – 9626 people. Among the militia, 3 % were those with higher and incomplete higher education, 13 % – secondary, 25 % – below secondary and 57 % – lower education. Ukrainians in the PCIA of the USSR in 1945 accounted for 55 %, Russians – 35 %, Jews – 4 %, Belarusians – 2 %, others – 2,6 %. In general, in 1945 the People's Commissariat of Internal Affairs and its subdivisions carried out significant and diverse work to improve the staff of the republic's militia.